The effect of breastfeeding education given through the teach-back method on mothers' breastfeeding self-efficacy and breastfeeding success: a randomized controlled study - Elif Ocaktan Çetindemir; Eda Cangöl (BMC, 2024)
Abstract Background An individualized education using visual aids, allowing the woman to demonstrate what she has learned, and providing the opportunity for the woman to ask questions are important in terms of breastfeeding self-efficacy, breastfeeding success, and the sustainability of the education. This study is original in evaluating the effectiveness and sustainability of breastfeeding education provided through the teach-back method in terms of breastfeeding self-efficacy and success in a short period of time. Therefore, the aim of this study is to examine the impact of teach-back method on mothers' breastfeeding self-efficacy and breastfeeding success. Materials and methods This is a randomized controlled study. The population of this study consisted of women who gave birth in the obstetrics and gynecology department of a state hospital located in Çorlu, in the northwest region of Turkey, between March 2022 and August 2022. The sample of this study consisted of a total of 100 postpartum women, with 50 participants in the experimental group and 50 participants in the control group, who gave birth in the obstetrics and gynecology department of Çorlu State Hospital. Computer-assisted simple randomization was employed to ensure the homogeneous distribution of the women into the experimental and control groups. The women in the experimental group received education and counseling services using the Teach-Back Method, based on the content of the prepared Breastfeeding Education Guide. The control group mothers, on the other hand, received standard breastfeeding education and counseling services. The data were collected through face-to-face interviews during the first 24 h postpartum and at the 1-month follow-up visits. In the study, the data collection tools used were a Personal Information Form, LATCH Breastfeeding Assessment and Evaluation Scale, Postpartum Breastfeeding Self-Efficacy Scale (short form), and the Teach-Back Observation Tool. In the evaluation of the research findings, the SPSS (Statistical Package for the Social Sciences) version 25.0 (IBM Corp., Armonk, NY, USA) program was used for statistical analyses. Descriptive, graphical, and statistical methods were employed to examine whether the scores obtained from each continuous variable followed a normal distribution. The Kolmogorov-Smirnov test was used to assess the normality of the scores derived from a continuous variable using statistical methods. Results In the study, no significant difference was found in the distribution of the socio-demographic characteristics of the participants according to the study groups. In the experimental group, which received training with the tell-what-you-learned method, the mothers' average EÖYÖ scores before the training, at the 24th hour after the training and at the 1st month after the training were 46.41 ± 11.26, respectively; It was determined to be 66.23 ± 6.94 and 67.84 ± 6.27. In the measurements made during the follow-up, it was determined that there was a significant difference in the study group's EÖYÖ score averages (p < 0,001). For mothers in the experimental group, the average LATCH score of the mothers before training, 24 h after training and 1 month after training was 7.73 ± 1.81, respectively; It was determined that these values were 8.66 ± 1.61 and 9.95 ± 0.30, and there was a significant difference in the mean LATCH scores of the study group in the measurements made during the follow-up (p < 0.001). Conclusions Breastfeeding education provided through the teach-back method is more effective in increasing both breastfeeding success and breastfeeding self-efficacy when compared to standard breastfeeding education. Trial registration Iran Randomized Clinical Trial Center IRCT20220509054795N2 Date of first registration: 10/11/2022.